2007
DOI: 10.1158/1078-0432.ccr-07-0665
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induction in Human Melanoma Cells by Inhibition of MEK Is Caspase-Independent and Mediated by the Bcl-2 Family Members PUMA, Bim, and Mcl-1

Abstract: Purpose: Given that inhibitors of mitogen-activated protein (MAP)/extracellular signalregulated kinase (ERK) kinase (MEK) are being introduced into treatment for melanoma, the present study was carried out to better understand the mechanism by which they may induce apoptosis of melanoma cells. Experimental Design: A panel of human melanoma cell lines and fresh melanoma isolates was assessed for their sensitivity to apoptosis induced by the MEK inhibitor U0126. The apoptotic pathways and regulatory mechanisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
145
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 29 publications
15
145
2
1
Order By: Relevance
“…63 In a separate study, melanoma cell lines with high levels of ERK1/2 signalling underwent apoptosis when treated with U0126 and the increase in BIM and PUMA and the loss of MCL-1 appeared to play the critical role in cell death. 64 ERK1/2 signalling can also provide protection against chemotherapeutic cytotoxic drugs. In BRAF V600E -positive melanoma cells ERK1/2 signalling protects against apoptosis induced by cisplatin, actinomycin D or daunorubicin.…”
Section: Badmentioning
confidence: 99%
“…63 In a separate study, melanoma cell lines with high levels of ERK1/2 signalling underwent apoptosis when treated with U0126 and the increase in BIM and PUMA and the loss of MCL-1 appeared to play the critical role in cell death. 64 ERK1/2 signalling can also provide protection against chemotherapeutic cytotoxic drugs. In BRAF V600E -positive melanoma cells ERK1/2 signalling protects against apoptosis induced by cisplatin, actinomycin D or daunorubicin.…”
Section: Badmentioning
confidence: 99%
“…[12][13][14][15] Wild type p53 exists as a dimer or oligmer at the mitochondrial membrane and binds via its DNA binding domains with Bcl2 forming an inhibitory complex. Such binding disrupts the anti-apoptotic Bcl2/BAX ratio and results in outer mitochondrial membrane permeability and the release of toxic peptides from the outer compartment of the mitochondrion resulting in apoptosis.…”
Section: Wild Type P53 Protein Is Upregulated In Lch Following Treatmmentioning
confidence: 99%
“…This signalling pathway appears to be involved in prostate cancer drug resistance [7,8]. Furthermore, previous research has shown that inhibition of just one of the signalling proteins in this pathway can induce ap-npg optosis through down-regulation of myeloid cell leukaemia 1 (MCL-1), an anti-apoptotic member of the B-cell lymphoma 2 (BCL-2) gene family [9,10]. MCL-1 is expressed in a fairly high percentage of prostate tumours [11,12], and the inhibition of ERK pathway-mediated signals, and consequently expression of MCL-1, might be a key target for treatment of advanced prostate cancer cells, as suggested by Cavarretta et al [13].…”
Section: Introductionmentioning
confidence: 99%